Journal of Applied Electrochemistry - Botte, Geradine G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The Journal of Applied Electrochemistry is the leading journal on technologically orientated aspects of electrochemistry. The interface between electrochemical science and engineering is highlighted, emphasizing the application of electrochemistry to technological development and practice, and documenting properties and data of materials; design factors, design methodologies, scale-up, economics and testing of electrochemical devices and processes. The broad range of technologies includes energy conversion, conservation, and storage, new battery systems, fuel cells, super capacitors, solar cells, power delivery, industrial synthesis, environmental remediation, cell design, corrosion, electrochemical reaction engineering, medical applications of electrochemistry and bio-electrochemistry, the electrochemical treatment of effluents, hydrometallurgy, molten salt and solid state electrochemistry, surface finishing, electroplating, electrodeposition, sensors, and applications of molecular electrochemistry. It also publishes invited reviewed articles, book reviews and news items and a comprehensive electrochemical events calendar.
Keywords: Physical chemistry; Electrochemistry; Chemical engineering; Electrochemistry; Physical Chemistry; Industrial Chemistry/Chemical Engineering